In Vitro Activities of DC-159a, a Novel Fluoroquinolone, against Mycobacterium Species - Disratthakit, Areeya (American Society for Microbiology (ASM), 2010)
The in vitro activities of DC-159a against seven species of Mycobacterium were compared with moxifloxacin, gatifloxacin, levofloxacin, and rifampin. DC-159a was the most active compound against quinolone-resistant multidrug-resistant M. tuberculosis (MIC(90), 0.5 μg/ml) as well as drug-susceptible isolates (MIC(90), 0.06 μg/ml). The anti-tubercle bacilli activity of DC-159a was 4- to 32-fold more potent than those of currently available quinolones. DC-159a also demonstrated the highest activities against clinically important nontuberculous mycobacteria.